Teachers’ and Parents’ Roles in Shaping Children’s Learning Behavior in the Digital Era at the Indonesia–Malaysia Borderland - Dwi Surti Junida; Nurmila Sari Djau (CV. Yazri Aksara Nusantara, 2026)
This study examines the roles of teachers and parents in shaping children's learning behavior in the digital era within the Indonesia–Malaysia borderland. A qualitative case study approach was employed in Entikong, West Kalimantan, involving an experienced elementary school teacher as the primary informant. Data were collected through a semi-structured interview and analyzed using thematic analysis. The findings indicate that digital technology functions as both a learning resource and a source of distraction. Children's learning behavior is influenced by parental supervision, teacher guidance, school regulations, and broader social environments. While digital platforms provide opportunities for accessing information and supporting independent learning, challenges related to excessive technology use, declining learning discipline, and changing social behavior remain evident. The study highlights the importance of collaboration between families and schools in promoting responsible technology use and positive learning habits. These findings contribute to understanding children's learning behavior in digitally connected borderland communities. Penelitian ini bertujuan mengkaji peran guru dan orang tua dalam membentuk perilaku belajar anak pada era digital di wilayah perbatasan Indonesia–Malaysia. Penelitian menggunakan pendekatan studi kasus kualitatif yang dilaksanakan di Entikong, Kalimantan Barat, dengan melibatkan seorang guru sekolah dasar berpengalaman sebagai informan utama. Data dikumpulkan melalui wawancara semi-terstruktur dan dianalisis menggunakan analisis tematik. Hasil penelitian menunjukkan bahwa teknologi digital berfungsi sekaligus sebagai sumber belajar dan sumber distraksi. Perilaku belajar anak dipengaruhi oleh pengawasan orang tua, bimbingan guru, regulasi sekolah, serta lingkungan sosial yang lebih luas. Meskipun platform digital menyediakan peluang untuk memperoleh informasi dan mendukung pembelajaran mandiri, tantangan berupa penggunaan teknologi yang berlebihan, menurunnya disiplin belajar, dan perubahan perilaku sosial masih ditemukan. Penelitian ini menegaskan pentingnya kolaborasi antara keluarga dan sekolah dalam membangun penggunaan teknologi yang bertanggung jawab serta perilaku belajar yang positif pada komunitas perbatasan yang semakin terhubung secara digital.